Black Root Rot of Strawberry: A Disease Complex - Kumari, Neelam; Thakur, Ashok (International Journal of Economic Plants, 2022)
Historically, root diseases have been a production-limiting problem for the strawberry industry worldwide. Even though this disease is of great economic importance, the etiology remains unresolved. However, soilborne fungal root pathogens, particularly Pythium and Rhizoctonia spp. have been implicated as major role players. Presence of nematodes in soil and favourable environmental conditions also play significant role in the disease development. Development of integrated disease management strategies is dependent upon a more complete understanding of the etiology, biology and ecology of the disease complex.